PENGARUH PEMBERIAN BOKASHI DAUN GAMAL TERHADAP SERAPAN FOSFOR DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccarata) PADA ENTISOL SIDERA - rl, Rifka oktafiani; Wahyudi, imam; Ali, Ramlan (AGROTEKBIS, 2018)
This study aimed to determine the effect of the application of Gamal Bokashi on Entisol Sidera on nitrogen uptake and yield of sweet corn in Entisol Sidera. The research used a randomized block design with five treatments ie. g0 = control, g1 = 10 t ha-1, g2 = 15 t ha-1, g3 = 20 t ha-1, g4 = 25 t ha-1-, g5 = 30 t ha-1, c6 = 35 t ha-1. Each treatment was replicated three times so that three were 21 experimental units. This research used sweet corn as an indicator plant with variable observed including soil pH, soil C-organic, soil P- total content, P-available, P concentration plant tissue, plant dry weight, P uptake, and yield of sweet corn crop production. The results showed that administration of Bokashi with a dose of 35 ton ha-1 can increase soil pH, soil C-organic, soil P- total content, P-available, P concentration plant tissue, plant dry weight, P uptake, and yield of sweet corn crop production.Key word : Bokashi Leaves Gamal, P Uptake, Sweet Corn, Entisol.